The Russian Urban System in Transition: The View of New Economic Geography - Albrecht Kauffmann (European Regional Science Association (ERSA), 2013)
After the price liberalization in 1991, the Russian economy was faced with a jump of costs of transportation in real terms. New Economic Geography (NEG) gives answers to questions that are related to changes in transport costs. However, the outcomes of NEG models are very sensitive with respect to their basic assumptions. Using an alternative model framework including urban costs, it is shown that also increasing costs of freight transportation may give incentives to migration of skilled workers from remote, small urban units to central, large cities. Therefore, concentration of urban population should have been increased. But, one cannot expect that this process is reversible, if transportation costs are decreasing in the future due to improvements in the transportation sector. On the contrary, large agglomerations will then grow even more. Research questions are: What were the relations between urban growth and urban size in Russia during the transformation period? Are migration flows correlated to changes in concentration of urban population? In the empirical investigation, population figures 1993?2004 of all Russian cities and urban settlements have been used, together with geographical coordinates of all urban units. On the regional level, demographic data (natural growth, matrices of urban and rural migration, external migration) were available for the federal subjects of Russia. The peculiarities resulting from so called ?secret cities? have been considered. The empirical part of the paper contains two regression analyses using OLS method: firstly, urban size and geographical position are regressed on urban growth; secondly, migration volumes are regressed on changes in urban concentration. Urban-rural as well as rural-urban migration has been introduced into the statistical models as control variables. The main results of this analysis are: Firstly, urban growth in Russia is positively correlated to the initial size of cities and settlements as well as to their geographical position. Secondly, there is a link between increasing concentration of urban population and migration flows of urban dwellers who reside in different federal subjects of Russia. Although internal migration flows in the 1990ties and the early 2000s were relatively weak, they influenced urban concentration as NEG predicts. From the viewpoint of New Economic Geography, urban costs are an important factor that has strong dispersing effects. Therefore, to make use of the advantages of large agglomerations in Russia, it is required to improve the performance of the transportation sector, to diminish the costs of transportation between cities, as well as within cities.
Keywords: O18; P25; J61; 330; Russia; Urban Systems; Migration; New Economic Geography